Auditoría administrativa y su relación con el desarrollo organizacional de la empresa agrícola “Benítes”, del cantón La Maná, año 2012 - Santana Soledispa, Germania Liliana (2015)
This research was conducted at the Agricultural "Benites" Canton La Mana, and different research methods to produce the report were used. It began with the application of questionnaires, then observations, interviews and notes were made; administrative area information was gathered, and made a brief but necessary general knowledge of the area that generates information for the products it sells. With the knowledge gained was reached defining the problem which is to solve the organizational structure. And the identification of the problem was necessary to consult the theory through a comprehensive review, to have knowledge regarding organizational design techniques and solve the identified situation. Based on the methodology specified in the audit plan; we as initial preliminary diagnosis which made it possible to obtain a general understanding of the entity and the processes that make up the audited system. Subsequently, the internal control was assessed by COSO I system, called risk and audit approach was established. In the second stage audit testing it was applied, using procedures based on the results of the evaluation of internal control, obtaining sufficient, competent, and relevant evidence to support the findings. In the final stage it disclosed the comments, conclusions and recommendations aimed at improving the organizational development of the agricultural company "Benites" Canton La Maná, 2012.